316 W high-brightness narrow-linewidth linearly-polarized all-fiber single-frequency laser at 1950 nm. (21st October 2021) - Guan, Xianchao; Yang, Changsheng; Gu, Quan; Lin, Wei; Tan, Tianyi; Zhao, Qilai; Wei, Xiaoming; Yang, Zhongmin; Xu, Shanhui
Abstract: Based on a three-cascaded all-fiber master oscillator power-amplifier configuration, a 1950 nm high-brightness narrow-linewidth linearly-polarized single-frequency fiber laser with an output power of 316 W and a laser linewidth of 8.4 kHz is demonstrated experimentally. With the employment of a square-coiling fiber scheme with round corners and a 20/300 μ m-core/cladding polarization-maintaining Tm 3+ -doped double-cladding fiber, the bending loss of LP11 mode is improved, thus leading the good beam quality, Mx 2  = 1.19 and My 2  = 1.17, herein. Additionally, a polarization-extinction ratio of 17.1 dB and an optical signal-to-noise ratio of >63 dB separately confirm good maintenance of linear polarization and adequate suppression of amplified spontaneous emission in the power amplification.